British Monarchy: from the Past to the Future? - Galina S. Ostapenko; Ludmila V. Arkhipova (Научно-аналитический вестник Института Европы РАН)
The article shows the traditions of the British monarchy and at the same time steps towards its modernization. The authors return to long-standing discussions about the possibility of republicanism prevailing in the United Kingdom. The work highlights the foundations of the British monarchy; Republican trends in the activities of T. Hardy’s Independent Labor Party, other political organizations, Conservative and Labor governments, individual prime ministers and social and political figures are examined. The efforts of the anti-monarchist group «Republic» are assessed. The authors analyzed the periods of the so-called crisis of the «model family of the nation», relying on the publications of British biographers on individual members of the royal family. The article reveals the attitude of the British towards the monarchy, King Charles III and the royal family according to the results of public opinion polls. It could be argued that at this stage most Britons view the monarchy and the reign of Charles III with approval.